Evaluation of the eruption of permanent teeth and their association with malocclusion - Anita Fekonja (Wiley, 2022)
Abstract Objectives This study was done to determine the timing of eruption of permanent teeth by sex and the number of permanent teeth erupted at different ages and to assess its association with malocclusion. Material and Methods The sample for this study consisted of 633 healthy subjects (317 boys and 316 girls) aged between 5.0 and 15.0 years. The subjects were divided into subgroups considering an age interval of 1 year. Results The mean eruption times were lower for girls compared with boys except for the maxillary and mandibular second premolars and second molars, which were found to erupt earlier in boys. All the permanent mandibular teeth, except the second premolars, tended to erupt earlier than their maxillary antagonists in both sexes. The sequence of eruption differs between girls and boys in the maxillary canine and maxillary second premolars. In Class III malocclusion, all the permanent mandibular teeth erupt earlier than their maxillary antagonists. In the entire sample, the correlation between the number of erupted teeth and age was strong (p < .05), but the differences between sexes were not significant. Conclusions It is important to know the normal eruption time of permanent teeth in the population due to diagnosis and better treatment planning in pediatric dentistry and orthodontics.